Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0438
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Ultra-Heavy Galactic Cosmic Rays from the SuperTIGER Instrument

Abstract: The SuperTIGER (Trans-Iron Galactic Element Recorder) experiment was launched on a longduration balloon flight from Williams Field, Antarctica, on December 8, 2012. SuperTIGER flew for a total of 55 days at a mean atmospheric depth of 4.4 g/cm 2 . The instrument measured the abundances of galactic cosmic rays in the charge (Z) range Z ≥ 10 with excellent charge resolution, displaying well resolved individual element peaks for 10 ≤ Z ≤ 40. SuperTIGER collected ∼ 3.95 × 10 6 Iron nuclei, ∼ 7.1 times as many as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…We have previously reported relative abundances of ultraheavy elements (30≤Z≤40) in SuperTIGER data that are consistent with earlier TIGER results and that support galactic cosmic ray origins in OB associations with preferential acceleration of refractory elements over volatile elements [2]. We have also reported relative abundances of iron secondaries, e.g.…”
Section: Introductionsupporting
confidence: 90%
“…We have previously reported relative abundances of ultraheavy elements (30≤Z≤40) in SuperTIGER data that are consistent with earlier TIGER results and that support galactic cosmic ray origins in OB associations with preferential acceleration of refractory elements over volatile elements [2]. We have also reported relative abundances of iron secondaries, e.g.…”
Section: Introductionsupporting
confidence: 90%
“…Elements above Fe are extremely rare compared to light elements, but they can provide unique information about the site of acceleration of GCRs. Measurements of the abundances of elements from Z=30 to Z=38 by the Trans-Iron Galactic Element Recorder (TIGER) [52] and the ratios of 22 Ne/ 20 Ne, 58 Fe/ 56 Fe, and C/O [53] by the Cosmic Ray Isotope Spectrometer (CRIS) onboard the Advanced Composition Explorer (ACE), support the idea of OB associations as CR acceleration sites. Since supernovae (SN) explode preferentially in groups of massive stars, named OB associations, then DSA would occur in an ISM of solar-system composition enriched in freshly synthesized material from previous SN or Wolf-Rayet star ejecta.…”
Section: Iron and Ultra-heavy Nucleimentioning
confidence: 91%
“…6(b). By assuming this source mixture, a clear separation of refractory and volatile elements and a better ordering by mass is obtained with respect to a pure solar system composition, indicating that the refractory elements (found in interstellar dust grains) are more effectively accelerated than volatile ones (present in interstellar gas) [56]. These preliminary measurements are consistent with previous observations by TIGER and ACE-CRIS (performed in a lower energy range, 150-600 MeV/n), and provide an improved test of the origin of GCR in OB associations and the volatility model of GCR acceleration.…”
Section: Iron and Ultra-heavy Nucleimentioning
confidence: 98%
See 1 more Smart Citation
“…For elements above 28 Ni a model prediction is needed to establish charge bands. We found that the Voltz et al [30] model discribes the SuperTIGER data best and it has been used to establish charge bands for the Below C0 events (see [31]). For the Above C0 events both Cherenkov counters are used to determine charge.…”
Section: Pos(icrc2015)038mentioning
confidence: 98%